CAVIN-2 positively correlates with diabetic PAD and promotes LDL transcytosis by inhibiting eNOS activation - Li Wang; Yi Song; Yan Shu; Baorui Xue; Fangyang Yu; Yao Yin; Ziyun Feng; Xiang Ma; Yulin Yao; Yangze Pan; Si Jin (Annals of Medicine)
Objective Caveolae are closely linked to the onset and progression of atherosclerosis. The pivotal involvement of caveolin-1 (CAV1) within the caveolae in atherosclerosis development has been consistently supported. However, the potential contributions of additional caveolae proteins to atherosclerosis necessitate further exploration. Therefore, this research aimed to afford clinical evidence linking CAVIN-2 to diabetic peripheral artery disease (PAD) and its role in low-density lipoprotein (LDL) transcytosis.Methods Blood samples were collected from a total of 115 participants, including 36 patients without diabetes (ND), 26 patients with type 2 diabetes mellitus (T2DM), and 53 patients with T2DM and PAD (DM-PAD). The plasma levels of CAV1, CAVIN-1, and CAVIN-2 were measured by ELISA. The correlation between CAV1, CAVIN-1, CAVIN-2, and diabetic PAD was examined using Spearman correlation analysis. The predictive effect of CAV1 and CAVIN-2 were analyzed by receiver operating characteristic (ROC) curves. Cellular experiments were used to investigate the effect and mechanism of CAVIN-2 on LDL transcytosis.Results Elevated CAV1 and CAVIN-2 levels were observed in T2DM and DM-PAD groups, with a positive correlation to DM-PAD and PAD severity. Both CAV1 and CAVIN-2 emerged as predictors of DM-PAD. In vitro, CAVIN-2 knockdown decreased LDL transcytosis, while CAVIN-2 overexpression increased it. Additionally, CAVIN-2 was found to inhibit eNOS activation and nitric oxide (NO) production, thereby promoting LDL transcytosis and atherosclerosis progression.Conclusion CAVIN-2 was positively correlated with DM-PAD and promoted LDL transcytosis through the inhibition of eNOS activation, contributing to atherosclerosis development. This study provided clinical evidence linking CAVIN-2 to diabetic PAD and suggested its potential as a biomarker for disease progression.